FABP3, FABP4, and heart rate variability among patients with chronic schizophrenia - Hung, Wei-Chin; Yu, Teng-Hung; Wu, Cheng-Ching; Lee, Thung-Lip; Tsai, I-Ting; Hsuan, Chin-Feng; Chen, Chun-Yu; Chung, Fu-Mei; Lee, Yau-Jiunn; Tang, Wei-Hua (Frontiers in Endocrinology, 2023)
The prevalence of cardiovascular disease (CVD) and CVD-related deaths in patients with schizophrenia is high. An elevated risk of CVD has been associated with low heart rate variability (HRV). There is increasing evidence that fatty acid-binding protein (FABP)3 and FABP4 play roles in the development and progression of CVD. This study aimed to explore the association of circulating FABP3/FABP4 levels with HRV in patients with chronic schizophrenia. We included 265 consecutive patients with chronic schizophrenia who attended a disease management program. We used an enzyme-linked immunosorbent assay for the measurement of plasma concentrations of FABP3 and FABP4. Standard HRV was recorded at baseline following a standard protocol. Mean high- and low-frequency (HF/LF) HRV values were analyzed by tertile of FABP3 and FABP4 using one-way analysis of variance, and linear regression analysis was performed to assess trends. A positive association between FABP3 and creatinine was found in multiple regression analysis. In addition, negative associations between levels of hematocrit, hemoglobin, HF HRV, and estimated glomerular filtration rate (eGFR) with FABP3 were also found. Moreover, positive associations between FABP4 with body mass index, diabetes mellitus, hypertension, systolic blood pressure, low-density lipoprotein-cholesterol, triglycerides, creatinine, and FABP3 were found. Furthermore, negative associations between levels of high-density lipoprotein-cholesterol, eGFR, and HF HRV with FABP4 were found. We also found a significant inverse association between FABP3 and HF HRV (p for trend = 0.008), and significant inverse associations between FABP4 with HF and LF HRV (p for trend = 0.007 and 0.017, respectively). Together, this suggests that elevated levels of FABP3 and FABP4 may be linked to health problems related to CVD in patients with chronic schizophrenia.